THE CORRELATION BETWEEN STUDENTS’ READING HABIT OF ENGLISH TEXT AND VOCABULARY ACHIEVEMENT AT THE NINTH GRADER STUDENTS OF SMPN 192 JAKARTA - Ria Yuliasari; Suwantica Kusumandari,; Ferdias Prihatnasari; Rina Lestari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine whether there is a significant relationship between reading habits of text and student vocabulary achievement or not. This research was conducted in ninth grade students of SMP 192 Jakarta. Samples were taken as many as 36 students in IX-4 based on the Random Sampling Cluster Technique. The research method used is Ex-Post Facto, meaning that the research is conducted after the facts occur and the data are available. So, the authors only see the effect on the dependent variable based on the documentary supported by library references. Data from the independent variables were collected by questionnaire test techniques and the dependent variables were collected by subjective test techniques. The results of statistical calculations using the Product Moment Test are 0.879. The r-table value of the significant level is 0.05 and the degree of freedom (N-2) = 34 is 0.339. Interpretation of the rxy value to the r-table value is obtained that rxy is higher than r-table (0.879> 0.339). Therefore, the null hypothesis (H0), which says that there is no correlation between students' reading habits in English texts and vocabulary achievement in ninth grade students of SMP 192 Jakarta, is rejected. Meanwhile the alternative hypothesis (Ha), which says that there is a relationship between the reading habits of English text students and vocabulary achievement in ninth grade students of SMP 192 Jakarta, is accepted based on a 5% significance level.